2006
DOI: 10.1021/jp062291p
|View full text |Cite
|
Sign up to set email alerts
|

Theoretical Investigation of Hydrogen Bonds between CO and HNF2, H2NF, and HNO

Abstract: Ab initio quantum mechanics methods were applied to investigate the hydrogen bonds between CO and HNF2, H2NF, and HNO. We use the Hartree-Fock, MP2, and MP4(SDQ) theories with three basis sets 6-311++G(d,p), 6-311++G(2df,2p), and AUG-cc-pVDZ, and both the standard gradient and counterpoise-corrected gradient techniques to optimize the geometries in order to explore the effects of the theories, basis sets, and different optimization methods on this type of H bond. Eight complexes are obtained, including the two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
18
0

Year Published

2008
2008
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 28 publications
(18 citation statements)
references
References 19 publications
0
18
0
Order By: Relevance
“…Figure 10 showed the FTIR spectra of RSF‐PBS, AEAPTES‐RSF‐PBS, and AEAPTMES‐RSF‐PBS, the stretching band of RSF‐PBS at ∼ 1715 cm −1 was assigned to the carbonyl groups of PBS, while the bands at 1722 and 1731 cm −1 were attributed to hydrogen‐bonded carbonyl groups,33–38 the formation of which caused a blue‐shift 39. The peaks occurring at different locations were assigned to hydrogen‐bonds and double contract hydrogen‐bonds 40–41. Therefore the results indicated that the surface amine of AEAPTES‐ and AEAPTMES‐treated RSF attack the PBS polymer through the hydrogen‐bonds and thus increased the interfacial adhesion.…”
Section: Resultsmentioning
confidence: 96%
“…Figure 10 showed the FTIR spectra of RSF‐PBS, AEAPTES‐RSF‐PBS, and AEAPTMES‐RSF‐PBS, the stretching band of RSF‐PBS at ∼ 1715 cm −1 was assigned to the carbonyl groups of PBS, while the bands at 1722 and 1731 cm −1 were attributed to hydrogen‐bonded carbonyl groups,33–38 the formation of which caused a blue‐shift 39. The peaks occurring at different locations were assigned to hydrogen‐bonds and double contract hydrogen‐bonds 40–41. Therefore the results indicated that the surface amine of AEAPTES‐ and AEAPTMES‐treated RSF attack the PBS polymer through the hydrogen‐bonds and thus increased the interfacial adhesion.…”
Section: Resultsmentioning
confidence: 96%
“…Previous computational studies showed that both the carbon and oxygen of CO are capable of hydrogen bonding, but a stronger interaction was observed for C···H as compared to O···H. 88,89 Therefore, CO likely interacts with the hydrogens of α-Zn 3 (HCOO) 6 via the carbon atom. Consistent with the apparent 13 C CS parameters, motional simulation results also revealed unidirectional trends in α and β as a function of temperature.…”
Section: Resultsmentioning
confidence: 99%
“…HNO can form various kinds of complexes with non-metal molecules, such as CO [31], HNO [32,33], HOX (X = F, Cl, Br, I) [34], CH 3 X (X = F, Cl, Br) [35], HFSO 2 [36], CH 3 CHO [37], HCONH 2 [38], XCHY (X = H, F, Cl, Br, CH 3 ; Y = O, S) [39], C 2 H 2 [40], HArF [41], and O 3 [42]. Based on the computational investigations, it is interesting to note that in these complexes, as long as the geometries allow, the most stable isomers prefer to involve both the terminal H and O atoms of HNO in the interactions, as illustrated in Fig.…”
Section: Interactions Between Hno and Non-metal Moleculesmentioning
confidence: 99%